Pengaruh Brand Campaign Dan Brand Awareness Di Tiktok Terhadap Keputusan Pembelian Produk Animate (Studi Kasus Pada Mahasiswa Universitas Teuku Umar) - Nopita Rahmaniza (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to analyze the influence of brand campaigns and brand awareness on purchasing decisions for Animate products. A case study was conducted on Teuku Umar University students. This research uses a quantitative approach. Primary data was collected by distributing questionnaires to 96 Teuku Umar University student respondents, who were selected using the Accidental Sampling technique. The primary data collected was then analyzed using multiple linear regression analysis with the SPSS program. The results of primary data analysis show that: (1) The Brand Campaign variable (X1) partially has a positive and significant effect on Purchase Decisions (Y), with a significance value of 0.000. (2) The Brand Awareness variable (X2) partially has a positive and significant effect on Purchasing Decisions (Y), with a significance value of 0.000. (3) Simultaneously, Brand Campaigns and Brand Awareness have a significant effect on Purchasing Decisions. The coefficient of determination test (R2) shows that 82.3% of purchasing decisions are explained by these two variables, while the remaining 17.7% is influenced by other factors.